(untitled) (CIPEEX, 2026)
ABSTRACT Introduction: Test anxiety has been an object of investigation due to its negative consequences on academic performance and mental health in schoolchildren. For this reason, it is necessary to develop evidence-based interventions and accessible materials in educational settings. Methods: Applied research, with a quantitative approach and an exploratory-descriptive design, guided by the Design-Based Research (DBR) model, with the development of a flipbook in five stages: 1 - Problem analysis; 2 - Flipbook design and construction; 3 - Implementation; 4 - Validation with specialists in the areas of Physical Education, Psychology, Education, or related fields; and 5 - Product finalization. Results: It is expected that the study will contribute to the advancement of knowledge about test anxiety in the school context, highlighting physical activity as a coping strategy. In addition, the educational product may favor the emotional self-regulation of adolescents, promote physical and mental well-being, and, possibly, contribute to the improvement of academic performance. Conclusion: The proposed educational product, flipbook, may be configured as a preventive, accessible, non-pharmacological, and low-cost intervention. Keywords: test anxiety; physical activity; mental health